The role of Polycomb Repressive Complex 2 associated proteins in mediating complex recruitment - Brien, Gerard L. (Trinity College (Dublin, Ireland). Department of Genetics, 2013)
All multi-cellular organisms are constructed from a myriad of distinct cell types, each performing specialized functions. With very few exceptions all cell types contain the same genetic information encoded in the genome. Therefore, this specialization is achieved through specific gene expression programs. Cells need these gene expression programs to be maintained during growth and division throughout the entire life of the cell. This implies the presence of a ‘cellular memory’ system that ensures faithful transmission of pre-existing expression programs between mother and daughter cells.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin